A Practical Strategy for Exploring the Pharmacological Mechanism of Luteolin Against COVID-19/Asthma Comorbidity: Findings of System Pharmacology and Bioinformatics Analysis - Xie, Yi-Zi; Peng, Chen-Wen; Su, Zu-Qing; Huang, Hui-Ting; Liu, Xiao-Hong; Zhan, Shao-Feng; Huang, Xiu-Fang (Frontiers in Immunology, 2022)
Asthma patients may increase their susceptibility to SARS-CoV-2 infection and the poor prognosis of COVID-19. However, anti-COVID-19/asthma co-morbidity approaches are restricted on condition. Existing evidence indicates that luteolin has antiviral, anti-inflammatory and immune-regulation capabilities. We aimed to evaluate the possibility of luteolin evolving into an ideal drug and explore the underlying molecular mechanisms of luteolin against COVID-19/asthma co-morbidity. We used system pharmacology and bioinformatic analysis to assess the physicochemical properties and biological activities of luteolin, and further analyze the binding activities, targets, biological functions and mechanisms of luteolin against COVID-19/asthma co-morbidity. We found that luteolin may exert ideal physicochemical properties and bioactivity, and molecular docking analysis confirmed that luteolin performed effective binding activities in COVID-19/asthma co-morbidity. Further, a protein–protein interaction network of 538 common targets between drug and disease was constructed and 264 hub targets were obtained. Then the top 6 hub targets of luteolin against COVID-19/asthma co-morbidity were identified, including TP53, AKT1, ALB, IL-6, TNF and VEGFA. Furthermore, the enrichment analysis suggested that luteolin may exert effects on virus defence, regulation of inflammation, cell growth and cell replication and immune responses, reducing oxidative stress and regulating of blood circulation through Toll-like receptor, MAPK, TNF, AGE/RAGE, EGFR, ErbB, HIF-1, PI3K-AKT signaling pathways, PD-L1 expression and PD-1 checkpoint pathway in cancer. The possible “dangerous liaison” between COVID-19 and asthma is still a potential threat to world health. This research is the first to explore whether luteolin could evolve in to a drug candidate for COVID-19/asthma co-morbidity. This study indicated that luteolin with superior drug likeness and bioactivity has great potential to be used for treating COVID-19/asthma co-morbidity, but the predicted results still need to be rigorously verified by experiments.